Spatial Inequality in Hospital Accessibility and Urban Well-Being: Evidence of a Nonlinear Relationship Mediated by Demographic Change - Siyi Guo; Jiafeng Gu (Land, 2026)
Ensuring equitable access to healthcare services safeguards individual wellbeing and enhances society’s overall happiness. This study investigates the complex relationships between spatial hospital accessibility, spatial inequality, and urban wellbeing, focusing on the physical dimension of access measured by travel time. Using geospatial and economic data from 13,776 hospitals, this study reveals that inequality in hospital accessibility, as measured by the Gini coefficient, significantly and negatively impacts urban happiness. Additionally, the results reveal a nonlinear, inverted U-shaped relationship between hospital accessibility and city-level happiness, indicating an optimal threshold beyond which marginal benefits decline. Additionally, the results indicate a key mediating mechanism: unequal access drives population out-migration and reduces the permanent resident population. This outcome, in turn, partially transmits adverse effects to city-level wellbeing. These findings demonstrate substantial spatial and contextual heterogeneity, underscoring the need for policymakers to tailor urban health policies that prioritize enhancing accessibility and ensure equitable distribution to foster sustainable demographic stability and overall urban wellbeing.